PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE - Afriyola, Fingki; Rahmi, Rahmi; Delyana, Hafizah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Student learning independence is still lacking and student learning outcomes are still low is the background of this research. This study aims to determine the effect of students' mathematics learning independence after applying the Think Pair Share type cooperative learning model in class X SMKN 1 Ranah Ampek Hulu, Pesisir Selatan Regency. This study uses the One Shot Case Study research design. The data analysis technique used simple linear regression analysis. The questionnaire score regression coefficient (b) is 0.823 with a significant level of 0.05. Because the regression coefficient (b) is positive (+). So there is a positive influence between independent learning (X) on learning outcomes (Y). The closeness of the linear relationship between X and Y can be seen from the correlation coefficient r = 0.135 which means it is close to 0, so the linear relationship between X and Y is weak. The conclusion is that independent learning has an effect on student mathematics learning outcomes by using cooperative learning type Think Pair Share.